ANALISIS EFEKTIVITAS MESIN MOLDING INJECTIONDENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS DAN SIX BIG LOSSES SEBAGAI DASAR USULAN PERBAIKAN PADA CV. XYZ - Agusthina (2022)
CV. XYZ is a company engaged in manufacturing that produces products made from rubber, plastic, iron and steel. In this company there is a problem, one of which is regarding the maintenance of the machine, one of which is the injection molding machine which makes the machine run less effectively. So the problem to be discussed is knowing the effectiveness of the machine using the OEE method and then finding the biggest loss that affects the amount of OEE value. Then an analysis of the things that caused the greatest loss could occur using the FTA method and the FMEA weighting was carried out so that suggestions for improvements could be made using the 5W-1H method. After the calculation, the OEE value is 70.08% where this value is still below the standard set by the world. Then the biggest loss is idling and minor stoppages of 34.21% affecting the OEE value. After that, an analysis of the causes of idling and minor stoppages was carried out using the FTA method and the weighting using the FMEA method. Several reasons were found whose RPN value exceeded the average and then proposed improvements using the 5W-1H method including holding periodic training, making injection machine usage sips, making machine checking forms, improving the recording system to be more complete and clear, paying attention to the quality and age of each year. spare parts, making machines damaged, calculating the availability of materials properly, buying ezhaust and adjusting the electrical power needed.